METHODOLOGY OF USING DIGITAL TECHNOLOGIES IN TEACHING ENGLISH AT SECONDARY SCHOOL (Web of Teachers: Inderscience Research, 2026)
This article explores the methodology of integrating digital technologies into English language teaching (ELT) within secondary school environments. As digital fluency becomes a prerequisite for global communication, the traditional classroom must evolve to incorporate multimodal and interactive resources. This paper reviews current methodologies—including flipped classrooms, gamification, and AI-assisted learning—and analyzes their impact on student engagement, language acquisition, and the development of digital literacy. The findings suggest that when digital tools are strategically aligned with communicative language teaching (CLT) principles, they significantly enhance student outcomes, particularly in reading, writing, and listening comprehension.